Outcomes of patients with myocardial infarction and cardiogenic shock treated with culprit vessel-only versus multivessel primary PCI - Hlinomaz, Ota; Motovska, Zuzana; Kala, Petr; Hromadka, Milan; Precek, Jan; Mrozek, Jan; Červinka, Pavel; Kettner, Jiri; Matejka, Jan; Zohoor, Ahmad; Bis, Josef; Jarkovsky, Jiri (Hellenic journal of cardiology, 2024)
INTRODUCTION AND OBJECTIVES: Multivessel primary percutaneous coronary intervention (pPCI) is still often used in patients with ST-elevation myocardial infarction (STEMI) and cardiogenic shock (CS). The study aimed to compare the characteristics and prognosis of patients with CS-STEMI and multivessel coronary disease (MVD) treated with culprit vessel-only pPCI or multivessel-pPCI during the initial procedure. MATERIAL AND METHODS: From 2016 to 2020, 23,703 primary PCI patients with STEMI were included in a national all-comers registry of cardiovascular interventions. Of them, 1,213 (5.1%) patients had CS and MVD at admission to the hospital. Initially, 921 (75.9%) patients were treated with culprit vessel (CV)-pPCI and 292 (24.1%) with multivessel (MV)-pPCI. RESULTS: Patients with 3-vessel disease and left main disease had a higher probability of being treated with MV-pPCI than patients with 2-vessel disease and patients without left main disease (28.5% vs. 18.6%; p < 0.001 and 37.7% vs. 20.6%; p < 0.001). Intra-aortic balloon pump, extracorporeal membrane oxygenation (ECMO), and other mechanical circulatory support systems were more often used in patients with MV-pPCI. Thirty (30)-day and 1-year all-cause mortality rates were similar in the CV-pPCI and MV-pPCI groups (odds ratio, 1.01; 95% confidence interval [CI] 0.77 to 1.32; p = 0.937 and 1.1; 95% CI 0.84 to 1.44; p = 0.477). The presence of 3-vessel disease and the use of ECMO were the strongest adjusted predictors of 30-day and 1-year mortality. CONCLUSIONS: Our data from an extensive all-comers registry suggests that selective use of MV-pPCI does not increase the all-cause mortality rate in patients with CS-STEMI and MVD compared to CV-pPCI.
Keywords: Shock, Cardiogenic; infarkt myokardu; lidé; ST Elevation Myocardial Infarction; nemoci koronárních tepen; výsledek terapie; infarkt myokardu s elevacemi ST úseků; rizikové faktory; Humans; Myocardial Infarction; Coronary Artery Disease; Risk Factors; Treatment Outcome; koronární angioplastika; kardiogenní šok; Percutaneous Coronary Intervention